(untitled) (GUB Journal of Science and Engineering, 2020)
Duplicate content or writing on online social networks is a material that shows up in many more than one location on Online Social Site, Pages etc. Nowadays Facebook is an online social networking site that connects people together during the form of expressing personal preferences and opinions as well as communication. In this research paper, we found detecting duplicate material in Facebook groups, pages, and trying to provide a solution for limiting this duplicate content, that is being posted to Facebook and other online social networks. We specified the solution to the issue in the first step and designed an algorithm called Restriction Algorithm for Duplicate Content, which is restricted to posting the copied content in more times on social networks like Facebook. In the second step, we have implemented it to validate our methodology and we have checked the identification of duplicate content of social media writing by using various social media posts as input tests and finally enriching the findings at a satisfactory stage. With optimal computation time, our proposed algorithm can handle large string sizes (more than 10,000 bytes). GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 6(1), Dec 2019 P 33-38